IRF9 and unphosphorylated STAT2 cooperate with NF-κB to drive IL6 expression - Nan, Jing (Proc Natl Acad Sci U S A, 2018)
In response to IFNβ, the IL6 gene is activated, modestly at early times by ISGF3 (IRF9 plus tyrosine-phosphorylated STATs 1 and 2), and strongly at late times by U-ISGF3 (IRF9 plus U-STATs 1 and 2, lacking tyrosine phosphorylation). A classical IFN-stimulated response element (ISRE) at −1,513 to −1,526 in the human IL6 promoter is required. Pretreating cells with IFNβ or increasing the expression of U-STAT2 and IRF9 exogenously greatly enhances IL6 expression in response to the classical NF-κB activators IL1, TNF, and LPS. U-STAT2 binds tightly to IRF9, the DNA binding subunit of ISGF3, and also to the p65 subunit of NF-κB. Therefore, as shown by ChIP analyses, U-STAT2 can bridge the ISRE and κB elements in the IL6 promoter. In some cancer cells, the protumorigenic activation of STAT3 will be enhanced by the increased synthesis of IL6 that is facilitated by high expression of U-STAT2 and IRF9.